‘I am all alone’: factors influencing the provision of termination of pregnancy services in two South African provinces - Mantshi E. Teffo; Laetitia C. Rispel (Global Health Action, 2017)
Background: Globally, universal access to sexual and reproductive health care services has been re-emphasised. One-third of maternal deaths could be averted by improving access to safe abortion services. Anecdotal evidence suggests that the implementation of the Choice of Termination of Pregnancy Act has been suboptimal in South Africa. Objectives: In two South African provinces, determine: the proportion of designated termination of pregnancy (TOP) facilities that provide these services; explore the factors that influence the provision of TOP services; and explore the work experiences of health care providers at designated TOP facilities. Methods: During 2014 and 2015, we conducted a cross-sectional study at designated TOP facilities in Gauteng and North West provinces. A combination of methods was used, consisting of: site visits to, and observation of, each of the designated facilities using a checklist, and in-depth interviews with a sub-set of 30 TOP service providers, using a semi-structured interview schedule. The interview questions focused on the factors influencing TOP service provision, and the work experiences of TOP service providers. We used interpretative phenomenological analysis to analyse the data from the interviews. Results: Overall, 77% (47/61) of designated facilities were providing TOP services, with 87.5% (28/32) in Gauteng Province, compared with 65.5% (19/29) in North West Province. Service provision was influenced by health system deficiencies, human resource challenges, lack of prioritisation and lack of management support. Study participants reported a heavy burden of care provision and expressed an overwhelming feeling of loneliness, courtesy stigma and lack of support from other nurses and doctors, which further influence TOP service provision. Conclusions: South Africa has an enabling legal environment for the provision of TOP services. Supportive management, prioritisation of TOP services and employee wellness programmes to address the psychosocial issues experienced by providers are critical elements of an enabling health policy environment.